Design, synthesis, and antiprotozoal evaluation of new 2, 4-bis[(substituted-aminomethyl)phenyl]quinoline, 1, 3-bis[(substituted-aminomethyl)phenyl]isoquinoline and 2, 4-bis[(substituted-aminomethyl)phenyl]quinazoline derivatives. (1st January 2020) - Guillon, Jean; Cohen, Anita; Boudot, Clotilde; Valle, Alessandra; Milano, Vittoria; Das, Rabindra Nath; Guédin, Aurore; Moreau, Stéphane; Ronga, Luisa; Savrimoutou, Solène; Demourgues, Maxime; Reviriego, Elodie; et al.
Abstract: A series of new 2, 4-bis[(substituted-aminomethyl)phenyl]quinoline, 1, 3-bis[(substituted-aminomethyl)phenyl]isoquinoline, and 2, 4-bis[(substituted-aminomethyl)phenyl]quinazoline derivatives was designed, synthesised, and evaluated in vitro against three protozoan parasites ( Plasmodium falciparum, Leishmania donovani, and Trypanosoma brucei brucei ). Biological results showed antiprotozoal activity with IC50 values in the µM range. In addition, the in vitro cytotoxicity of these original molecules was assessed with human HepG2 cells. The quinoline 1c was identified as the most potent antimalarial candidate with a ratio of cytotoxic to antiparasitic activities of 97 against the P. falciparum CQ-sensitive strain 3D7. The quinazoline 3h was also identified as the most potent trypanosomal candidate with a selectivity index (SI) of 43 on T. brucei brucei strain. Moreover, as the telomeres of the parasites P. falciparum and Trypanosoma are possible targets of this kind of nitrogen heterocyclic compounds, we have also investigated stabilisation of the Plasmodium and Trypanosoma telomeric G-quadruplexes by our best compounds through FRET melting assays. Graphical Abstract: UF0001